2011
DOI: 10.1182/blood-2010-09-307454
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of L-asparaginase with methotrexate and dexamethasone (AspaMetDex regimen) in patients with refractory or relapsing extranodal NK/T-cell lymphoma, a phase 2 study

Abstract: IntroductionExtranodal natural killer (NK)/T-cell lymphoma, nasal type, is a rare and severe malignancy. It is more frequent in Asia and Central/South America than in Europe and North America. It is thought to arise from NK cells or, occasionally, from a subset of ␥␦ or ␣␤ cytotoxic T cells, and shows a tight association with Epstein-Barr virus (EBV). It is classically characterized by a cytoplasmic CD3 ⑀ phenotype, with no surface CD3 or T-cell receptor expression, no T-cell receptor gene rearrangements, an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
266
3
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 334 publications
(281 citation statements)
references
References 31 publications
7
266
3
5
Order By: Relevance
“…These factors make conducting a prospective clinical trial for this population difficult. To overcome these problems, most studies selected a setting of multinational clinical trials [12][13][14], although this set-up might generate some practical problems due to differences in health insurance systems in the participating countries. Some recent studies have enrolled both patients with newly diagnosed stage IV and those with relapsed or refractory disease into first-line treatment [12,14].…”
Section: Specific Factors In Trials For Disseminated Enklmentioning
confidence: 99%
See 2 more Smart Citations
“…These factors make conducting a prospective clinical trial for this population difficult. To overcome these problems, most studies selected a setting of multinational clinical trials [12][13][14], although this set-up might generate some practical problems due to differences in health insurance systems in the participating countries. Some recent studies have enrolled both patients with newly diagnosed stage IV and those with relapsed or refractory disease into first-line treatment [12,14].…”
Section: Specific Factors In Trials For Disseminated Enklmentioning
confidence: 99%
“…A French group conducted a multicenter phase II study of AspaMetDex (L-asparaginase, methotrexate, and dexamethasone) chemotherapy for relapsed or refractory ENKL [13]. This regimen was selected based on the promising results of their pilot study [57].…”
Section: Aspametdex Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…A phase 2 study that evaluated the efficacy and safety of SMILE therapy showed an excellent antitumor activity for patients with relapsed or refractory NKTCL, with an ORR of 77% and a 1‐year OS of 79% or 25%, respectively, and with a 3‐year OS of 50% 22, 52. Phase 2 studies of l ‐asparaginase, methotrexate, and dexamethasone, IMEP, and gemcitabine‐pegaspargase‐cisplatin‐dexamethasone also reported ORRs of 77%, 43%, and 88%, respectively 26, 53, 54…”
Section: Discussionmentioning
confidence: 99%
“…Asian and non‐Asian patients also experienced other non‐hematologic events such as hyperbilirubinemia and fibrinogenemia 19, 21, 22, 24, 25. These adverse events are frequently accompanied by hypersensitivity to l ‐asparaginase 21, 22, 26, 27. This enzyme is a key component of chemotherapy because of the selective inability of transformed lymphocytes to synthesize asparagine 28.…”
Section: Introductionmentioning
confidence: 99%